2018
DOI: 10.1186/s40645-018-0241-2
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory experiment on salt weathering by humidity change: salt damage induced by deliquescence and hydration

Abstract: A laboratory experiment on salt weathering was carried out under changing humidity conditions. Three types of rock (tuff and dense and porous sandstone) with sodium chloride, sodium sulfate, or magnesium sulfate were subjected to humidity oscillations from 20%RH to 98%RH during 6 h periods at 20°C. Prior to the weathering experiment, the rock specimens were oven-dried, and the water supply was restricted to only that from the air during the experiment. Salt on the rock specimens was deliquesced/hydrated at alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 60 publications
(57 reference statements)
1
29
0
Order By: Relevance
“…To obtain the mineral types and contents of the Yungang Grottoes sandstones, the samples at Grottoes 1,2,3,5,7,12,14,17,19,21,23,29 and 39 were collected. The XRD tests for these sandstones were conducted by the PetroChina Research Institute of Petroleum Exploration and Development.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the mineral types and contents of the Yungang Grottoes sandstones, the samples at Grottoes 1,2,3,5,7,12,14,17,19,21,23,29 and 39 were collected. The XRD tests for these sandstones were conducted by the PetroChina Research Institute of Petroleum Exploration and Development.…”
Section: Methodsmentioning
confidence: 99%
“…The hydration of sandstone has been investigated from various aspects. Rao [3] used the environmental scanning electron microscopy to observe the weathering process of sandstone; Grafchikov et al [4] investigated the weathering process of sandstone by X-ray fluorescence and other techniques; McCabe et al [5] investigated the influence of climate on the sandstone weathering in the UK; Barone et al [6] explored the effect of salt crystallization on the physical and mechanical properties of sandstone during weathering and Sato and Hattanji [7] investigated the weathering processes caused by different minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Sato and Hattanj [49] presented a study with a tuff and two sandstones. Comparing the tuff and a sandstone with similar porosity and tensile strength, the sandstone with higher micropore volume and higher specific surface behave worse while the tuff had large pores associated with the alteration of pumice.…”
Section: Multiple Factorsmentioning
confidence: 99%
“…Laboratory studies are, in general, more frequent than field studies (around 50% more), with diverse types of salts and weathering conditions (for recent reviews on laboratory salt weathering testing see Alves et al [5], Lubelli et al [6]). In the selected set, the main rock types are volcanic rocks (Seiki et al [3]; Yu & Oguchi [7]; Yavuz [8]; López-Doncel et al [9]; Germinario et al [10]; Özşen et al [11]; Çelik & Aygün [12]; Martínez-Martínez et al [13]; Pötzl et al [14]; Sato & Hattanji [15]; Zalooli et al [16]), being dominated by studies of pyroclastic rocks, and plutonic rocks (Cámara et al [4]; Yu & Oguchi [7]; López-Arce et al [17]; Silva et al [18]; Vázquez et al [19]; Cerrillo et al [20]; Martins et al [21]; Sousa et al [22]; Vázquez-Nion et al [23]; Graus et al [24]) with granite being dominant in this subset. In our present review we found fewer publications concerning laboratory testing of metamorphic rocks; most of them studying marbles (Vázquez et al [19]; Martínez-Martínez et al [25]; Navarro et al [26]; Vazquez et al [27]) with one studying gneiss (Ricardo et al [28]) but none in slates or schists.…”
Section: Analysis Of Publicationsmentioning
confidence: 99%